Method and system for monitoring pressure of natural gas pipeline based on AI edge calculation - ZHU LIYAN; JIANG WEIYANG; ZHOU SHAOYUN; YU CHENXING; LIU YANG; AO JIANFENG (2024)
The invention belongs to the technical field of natural gas pipeline monitoring. The invention provides a method and system for monitoring natural gas pipeline pressure based on AI edge calculation. The method comprises the following steps: constructing an AI edge prediction model; fitting the first pressure monitoring data set of each pressure monitoring point in the natural gas monitoring area into a pressure change curve; evaluating the leakage probability of each first pressure decline curve section in the pressure change curve by using a first AI edge prediction model to obtain a plurality of second pressure decline curve sections; receiving working state data of each gas consumption terminal associated with the corresponding pressure monitoring point, and performing secondary evaluation on each second pressure decline curve section based on each working state data by using a second AI edge prediction model to obtain a leakage probability of each second pressure decline curve section; when at least one s